Legal Construction of FPIC to Protect Ulayat Right - Samosir, Samuel Saut Martua; Rahayuningsih, Toetik (Arena Hukum, 2024)
This study explores the legal frameworks for protecting the ulayat rights of Indigenous peoples, focusing on their current challenges. Additionally, the study examines the role of the Free, Prior and Informed Consent (FPIC) policy as a potential solution for safeguarding these rights. The study employs a normative legal research method, incorporating four approaches: statutory, conceptual, case-based and comparative. It uses literature review techniques to analyse the legal issues, drawing on primary and secondary legal materials. Although the protection of Indigenous peoples’ ulayat rights is enshrined in various regulations and the constitution, the actual implementation of these protections falls short of expectations. Therefore, adopting FPIC as a national legal instrument is crucial. FPIC has been successfully implemented in countries like India and the Philippines, where it has proven effective in ensuring the active participation of Indigenous peoples in decisions that affect their rights.